2016
DOI: 10.1111/ane.12550
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver's burden in disorders of consciousness: a longitudinal study

Abstract: Although high level of burden was observed, it tends to decrease over time, except for financial burden. Hence, this study suggests the importance to plan strategies or targeted interventions in order to reduce the psychosocial and financial burden associated with caregiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…At one of the studies, it has been notified that the psychological burden of the caretakers of PVS patients was gradually decreasing after 2,5 years due to finding out that there are physical and psychological burdens and learning the strategies of how to cope with these burdens and stress while the economic burden was still affecting them negatively (11). In another study, the caretakers were going through high levels of long-term grief disorder and the coping strategies were being helpful (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At one of the studies, it has been notified that the psychological burden of the caretakers of PVS patients was gradually decreasing after 2,5 years due to finding out that there are physical and psychological burdens and learning the strategies of how to cope with these burdens and stress while the economic burden was still affecting them negatively (11). In another study, the caretakers were going through high levels of long-term grief disorder and the coping strategies were being helpful (18).…”
Section: Discussionmentioning
confidence: 99%
“…Among all of them, dealing with emotional problems, difficulties of giving care at home, and economic and social problems are the main issues (7,10). The need for long-term homecare for such patients are mostly fulfilled either by professionals in healthcare or social care (formal) or by family members, friends, people with no professional background (Informal) (11).…”
Section: Introductionmentioning
confidence: 99%
“…The experience of physical, financial and psychosocial dimensions of burden associated with caregiving for a family member with a disorder of consciousness , was investigated in nine of 18 studies, employing 4 different measures. Less than half of a sample of 48 participants were in paid employment with 30.6% of 48 participants experiencing financial problems over a two year period (33) and 38% in another study reported financial difficulties (31).…”
Section: Insert Table 2 Herementioning
confidence: 97%
“…Acquired brain injuries can result in severe disorders of consciousness, such as minimally conscious state (MCS), with often serious lifelong consequences for patients and their families [13]. Early onset of rehabilitation is a crucial factor with the goal of enhancing the patient’s consciousness by creating learning possibilities [4,5].…”
Section: Introductionmentioning
confidence: 99%